IMPROVING ENGLISH LITERACY THROUGH THE USE OF BILINGUAL STORYBOOKS AND DIGITAL TECHNOLOGY-BASED GAMES AT SLB B YAKUT PURWOKERTO - Laxmi Mustika Cakrawati; Weksa Fradita Asriyama; Slamet Riyadi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Students with disabilities have the same right to access education. Although in reality, teaching students with disabilities presents many challenges, teachers are still expected to facilitate students' learning needs so that students can get the best education. Teaching English to students with hearing disabilities presents its own challenges. Not only does English have different word and sentence structures from Indonesian, but the sign language used in Indonesian and English is also different. Due to these obstacles, English language learning at SLB B Yakut Purwokerto is not yet optimal. Therefore, through a program to improve English literacy through the use of bilingual storybooks and digital technology-based games, it is hoped that teachers can improve students' ability to acquire English vocabulary and use it in appropriate everyday contexts. The objectives of this community service program are 1) to describe the use of teaching media in English learning in the classroom, and 2) to identify the impact of the use of teaching media in improving the English literacy of students with hearing disabilities at SLB B Yakut Purwokerto. The methods used in this community service program included 1) coordination with the school through observation and discussion and 2) implementation of the community service program, which included the socialization of the community service program, discussion on the use of teaching media to optimize English language learning, practice in using teaching media, and program evaluation. The results of the activities showed positive responses from both teachers and students.